The genesis of budgetary federalism and interbudgetary relation formation and development in the Russian Federation - K. Shardan, Saida (2020)
Budgetary federalism in modern conditions acts as a key link in the financial system of the Russian Federation. And this is natural, because the efficiency of the entire budgetary system, and hence the economy of the national economy as a whole, depends on the effectiveness of budgetary federalism functioning. Of course, one can hardly overestimate the importance of budgetary federalism for such countries as Russia, the United States, Great Britain, the Federal Republic of Germany, and others, which are considered as a federal state. One of the most important problems in federal countries is the need to develop a modern economic mechanism for vertical alignment in order to distribute optimally the financial flows between the corresponding levels of the budget system.Another independent problem is the need for horizontal alignment,